Pengaruh Harga dan Kualitas Produk terhadap Minat Beli dan Keputusan Pembelian Brand Erigo pada Masyarakat Kota Depok - Sundari, Wulan; Lailla, Nor (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
The purpose of this study was to determine the effect of price and product quality on purchasing interest, and to determine the effect of price and product quality on purchasing decisions. This descriptive quantitative study used a purposive sampling technique, with a sample of 200 respondents using Erigo products in Depok City. The SmartPLS tool was used to analyze the data. The results showed that there was a positive and significant effect of price and product quality on purchasing interest, and there was a positive and significant effect of price and product quality on purchasing decisions. Overall, the results of this study prove that price and product quality have an effect on purchasing interest and purchasing decisions of the Erigo brand in the Depok City community.